IDENTIFIKASI CAPLAK KERAS (Acari : Ixodidae) PADA ULAR SANCA BATIK (Python reticulatus) DI KEBUN BINATANG GEMBIRA LOKA YOGYAKARTA - , INASA RAHMAWATI, drh. Ana Sahara, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sanca Batik snake (Pyhton reticulatus) is a species of snake that made often kept as pet. Ectoparasite infestation is one of the health problems that often arise in these animals is, especially hard ticks. This research aims to identify the hard ticks (Family Ixodidae) that infest Sanca Batik snake at Gembira Loka Zoo Yogyakarta. The ticks sample taken manually using tweezers and stored in a tube. Female ticks suck the blood that has been separated in a tube to lay their eggs, then the eggs were weighed using an electric scale. The eggs will hatch into larvae within a month, then the larvae were weighed using an electric scale. The samples tick made into slides preparat by removing the blood in the body tickand then tick dehydrated using multilevel alcohol and soaked in the clove oil. Tick identified microscopically using a binocular microscope with a magnification of 40x includes skutum, capitulum shape, basis capituli, palpus, the number of festoons and coxae. The results of counting the number of eggs in five female tick average 165-1174. Microscopic observations indicate male and female ticks have small eyes